Percutaneous nephrolithotomy: technique - Knoll, Thomas (World journal of urology, 2017)
Percutaneous nephrolithotomy (PCNL) is considered to be the first line of treatment for large renal stones. Though PCNL comes with higher morbidity, its efficacy is unbeaten by other minimally invasive modalities. However, potential complications, such as bleeding, occur. Improved skills and modifications of the procedure may reduce the probability of adverse outcomes. This article discusses the current trends and standards in PCNL technique with special focus on all important steps as positioning, access, instruments, dilation, disintegration, and exit, including outcomes, complication management, and training modalities.